Transformation of peat during drying and long-term agricultural use - Скрипніченко, С. В.; Коцюба, І. Г. (Scientific Progress & Innovations, 2016)
The results of years research and development impact of drainage on soil formation peat soils and environmentally friendly measures are presented, we offered their rational and effective use. It was determined that the rate of destruction linen is intensive in cultivated rotation. Drainage and long-term development of peat soils occur with significant changes in their properties: increasing the density of soil and ash, and the total moisture content decreases.